Causes of death following discharge after trauma in North Carolina. Issue 2 (February 2022) - Bryant, Mary K.; Aubry, Staci; Schiro, Sharon; Raff, Lauren; Perez, Arielle J.; Reid, Trista; Maine, Rebecca G.
Abstract : BACKGROUND: While a "fourth peak" of delayed trauma mortality has been described, limited data describe the causes of death (CODs) for patients in the years following an injury. This study investigates the difference in COD statewide for patients with and without a recent trauma admission. METHODS: This retrospective cohort study compared COD for trauma and nontrauma patients in North Carolina. Death certificates in NC's death registry were matched with the NC trauma registry between January 2013 and December 2018 using matching on name and date of birth. Patients who died during the index trauma admission were excluded. Underlying COD recorded on the death certificate were used for the primary analysis. RESULTS: Of 481, 415 death records, 19, 083 (4.0%) were linked to an alive discharge within the trauma registry during the study period. Prior trauma patients (PTPs) had a higher incidence of mental illness (9.2 vs. 6.1%), Alzheimer's (6.1% vs. 4.2%), and opioid-related (1.8% vs. 1.6%) COD compared to nontrauma patients, p < 0.05. Overall, suicide was higher in the nontrauma cohort (1.5% vs. 1.1%); however, PTP had higher incidences of death by motor vehicle collision and other injury (6.0% vs. 3.8%) and homicide (0.9% vs. 0.6%), p < 0.001. Prior trauma patients had 1.16 increased odds of an opioid-related death ( p = 0.009; 95% confidence interval, 1.04–1.29) compared with those without prior trauma. Younger PTP had a much higher rate of death from suicide (12.0%) compared with those 41 to 65 years (2.8%) and older than 65 years (0.2%; p < 0.001). Discharge to skilled nursing facility (odds ratio, 1.87; p < 0.05) and severe injury (odds ratio, 1.93; p < 0.05) were associated with early death after discharge (⩽90 days). CONCLUSION: After hospital discharge, PTPs remain at risk of dying from future trauma and opioid-related conditions. Prevention strategies for PTP should address the increased risk of death from a subsequent traumatic injury and the at-risk populations for early death after discharge. LEVEL OF EVIDENCE: Prognostic and Epidemiologic, Level IV. Abstract : Supplemental digital content is available in the text.